Clinical and Pathological Investigation of Nandus nandus Collected from Fish Markets of Mymensingh - Marma, K; Ahmed, GU; Faruk, MAR; Gosh, K (Progressive Agriculture, 2014)
An experiment was carried out in order to investigate the health status of Nandus nandus based on clinical and histopathological observation collected from three fish markets of Mymensingh district. The study was conducted for a period of six months from October 2005 to March 2006. Clinically, it was evident that fishes were more affected having scale loss and deep dermal ulceration in the months of December and January, which were observed in Sankipara Railway Crossing and Gollpukurpar markets. But fish appeared almost normal during October to November and February to March collected from the three fish markets. Histopathologically, marked necrosis, pyknosis, haemorrhage, vacuoles and fungal granuloma were observed in skin, muscle and kidney. Gills had monogenetic trematode, hypertrophy and melanomacrophages in December and January. Liver of examined fishes had less pathological signs compared to other organs. However, Nandus nandus was found more affected in Gollpukurpar and Sankipara Railway Crossing markets compared to K-R market. From overall observation, it could be concluded that fishes were severely affected by EUS and dactylogyrosis during the months of December and January. DOI: http://dx.doi.org/10.3329/pa.v18i2.18193 Progress. Agric. 18(2): 167 - 174, 2007